Discourse Analysis of Politeness Strategies in Social Media Comments Related to Gender Issues - Firayani, Firayani (Journal of Linguistica, 2025)
This study examines the use of politeness strategies in social media comments related to gender issues, addressing how online interaction, anonymity, and the loss of contextual cues shape discursive behavior. Using a qualitative discourse analysis approach, data were collected from selected public comment threads on platforms such as Instagram, TikTok, and X, followed by systematic coding based on Brown and Levinson’s politeness framework. The analysis identifies distinct gendered patterns in the use of politeness strategies: male users frequently employ bald-on-record and positive impoliteness through direct confrontation and sarcasm, while female users tend to use negative impoliteness, indirect criticism, and positive politeness supported by emotional markers such as humor and emojis. Positive politeness emerges as the dominant strategy across discussions, especially in comments aiming to build solidarity around gender equality, whereas negative politeness appears in attempts to negotiate disagreement respectfully. Impoliteness both direct and indirect intensifies in controversial discussions, influenced by anonymity, platform norms, and cultural expectations. The findings highlight that online politeness is not merely a linguistic choice but a digital-discursive practice reflecting power relations, gender norms, and ideological conflict in contemporary social media environments.